1992
DOI: 10.1159/000217331
|View full text |Cite
|
Sign up to set email alerts
|

All Trans Retinoic Acid in Primary and Relapsed Acute Promyelocytic Leukemia

Abstract: Background: Acute promyelocytic leukemia (APL) is frequently associated with disseminated coagulopathy (DIC), causing a high incidence of fatal bleeding complications despite induction chemotherapy administered immediately after diagnosis. APL is cytogenetically characterized by the translocation t(15;17) involving the region of the retinoic receptor Α gene. In vitro all trans retinoic acid (ATRA) exhibits a differentiation-inducing and antiproliferative capacity on APL-cell lines. Similar effects were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…All patients received ATRA 45 mg/m2/day for induction treatment, six of them in combination with cytostatic therapy (patients 1, 5, and 10 received a standard chemotherapy, "3 + 7", i.e., daunorubicin 60 mg/m 2 day 1-3, cytosine arabinoside 100 mg/m 2 day 1-7; patients 4, 6, and 7 received high-dose cytosine arabinoside chemotherapy 3 g/m 2 every 12 h for 2 days, as previously reported for hyperleukocytosis [5]. All patients received ATRA 45 mg/m2/day for induction treatment, six of them in combination with cytostatic therapy (patients 1, 5, and 10 received a standard chemotherapy, "3 + 7", i.e., daunorubicin 60 mg/m 2 day 1-3, cytosine arabinoside 100 mg/m 2 day 1-7; patients 4, 6, and 7 received high-dose cytosine arabinoside chemotherapy 3 g/m 2 every 12 h for 2 days, as previously reported for hyperleukocytosis [5].…”
Section: Patientsmentioning
confidence: 87%
See 1 more Smart Citation
“…All patients received ATRA 45 mg/m2/day for induction treatment, six of them in combination with cytostatic therapy (patients 1, 5, and 10 received a standard chemotherapy, "3 + 7", i.e., daunorubicin 60 mg/m 2 day 1-3, cytosine arabinoside 100 mg/m 2 day 1-7; patients 4, 6, and 7 received high-dose cytosine arabinoside chemotherapy 3 g/m 2 every 12 h for 2 days, as previously reported for hyperleukocytosis [5]. All patients received ATRA 45 mg/m2/day for induction treatment, six of them in combination with cytostatic therapy (patients 1, 5, and 10 received a standard chemotherapy, "3 + 7", i.e., daunorubicin 60 mg/m 2 day 1-3, cytosine arabinoside 100 mg/m 2 day 1-7; patients 4, 6, and 7 received high-dose cytosine arabinoside chemotherapy 3 g/m 2 every 12 h for 2 days, as previously reported for hyperleukocytosis [5].…”
Section: Patientsmentioning
confidence: 87%
“…This rearrangement results in a functionally altered retinoic acid receptor, thus explaining the response of promyelocytic blasts to all-trans retinoic acid (ATRA) as a differentiating agent in vitro and in vivo [2,3]. ATRA gives a high complete remission rate in APL patients and reduces the incidence of fatal disseminated coagulopathy significantly [3][4][5]. Nevertheless, patients maintained with ATRA alone have a high relapse rate and therefore need chemotherapeutic consolidation [6].…”
Section: Introductionmentioning
confidence: 99%
“…As occasionally reported in the literature, APL patients who enter remission after cytotoxic chemotherapy sometimes do so without experiencing marrow hypoplasia [21,33,51,56]. ATRA-induced remissions, however, consistently occur with out marrow hypoplasia [7,22,35,38,58]. Serial marrow sam ples taken from APL patients during ATRA treatment show progressive maturation of the abnormal promyelocytes, in cluding retention of Auer rods in granulocytes.…”
Section: Differentiating Agentsmentioning
confidence: 99%
“…The all-trans retinoic acid (ATRA) therapy of acute promyelocytic leukemia has become a prototype of differentiationinducing oncotherapy [1], yet maintaining remissions remains a challenge [2]. Muindi et al [3] reported that 'Relapsed patients showed a clinical resistance to ATRA due to progressive re duction of plasma concentrations, whereas the leukemic cells obtained at the time of relapse retained their in vitro sensiti vity ...…”
Section: Introductionmentioning
confidence: 99%